Pengetahuan Mahasiswa STIKES RS Husada dalam Memberikan Edukasi Kepada Pasien Diabetes Mellitus dengan Mengunakan Diabetes Self Management Education - Fendy Yesayas; Fatima Ura Pabanne; Yulian Heiwer; Yarwin Yari; Jolan Wenno (FORIKES, 2021)
Diabetes mellitus (DM) is a chronic non-communicable disease and one of the main public health problems in the world with an increase in new cases which continues to increase from year to year. The latest estimate of the International Diabetes Federation (IDF), there were 382 million people living with diabetes mellitus in the world in 2013 and in 2017 there were 451 million people with an age range of 18-99 years. This figure is estimated to increase to 693 million people in 2045, analyzing the knowledge of STIKES RS Husada students before and after being given diabetes self-management education in providing education to diabetes mellitus patients. The type of research carried out was a Quasi Experiment using the One Group Pre follow-up method. -Post Test is to see the knowledge of STIKES RS Husada students before and after being given Diabetes Self Management Education on the ability to provide education to diabetes millitus patients. There is a variable relationship between respondents and a history of having a family history of DM patients with knowledge before being given diabetes selfmanagement education, it was found a value of 0,000 and after being given diabetes self-management education it was found a value of Pvalue 0.009. There was a difference in Good Knowledge before being given diabetes self-management education as much as 44.2% and after being given diabetes self-management education as much as 71.2%, with a value of Pvalue 0.000. Based on the results of the estimated parameter test, the variable history of having a family of DM sufferers greatly influences the knowledge of students in providing education to DM sufferers with a value of 0.003. There are differences in knowledge Both before and after being given diabetes self-management education, this is obtained by having a family history of DM sufferers.Keywords: diabetes mellitus; knowledge; diabetes self management educationABSTRAKDiabetes Militus (DM) adalah penyakit kronik yang tidak menular dan salah satu menjadi masalah kesehatan utama masyarakat di dunia dengan peningkatan kasus baru yang terus meningkat dari tahun ke tahun. Estimasi terakhir International Diabetes Federation (IDF), terdapat 382 juta jiwa yang hidup dengan diabetes melitus di dunia pada tahun 2013 dan tahun 2017 terdapat 451 juta jiwa dengan rentang usia 18-99 tahun. Angka ini di perkirakan meningkat menjadi 693 juta jiwa di tahun 2045, Untuk menganalisis pengetahuan mahasiswa STIKES RS Husada sebelum dan sesudah diberikan diabetes self management education dalam memberikan edukasi kepada pasien diabetes mellitus, Jenis penelitian yang dilakukan adalah Quasi Eksperimen dengan menggunakan metode follow up dengan pendekatan desain One Group Pre – Post Test yaitu untuk melihat pengetahuan mahasiswa STIKES RS Husada sebelum dan sesudah diberikan Diabetes Self Management Education terhadap kemampuan dalam memberikan edukasi kepada pasien diabetes millitus. Terdapat hubungan variabel responden dengan riwayat memiliki keluarga penderita DM terhadap pengetahuan sebelum diberikan diabetes self management education ditemukan nilai Pvalue 0,000 dan sesudah diberikan diabetes self management education ditemukan nilai Pvalue 0,009. Terdapat perbedaan Pengetahuan Baik sebelum diberikan diabetes self management education sebanyak 44,2% dan sesudah diberikan diabetes self management education sebanyak 71,2%, dengan nilai Pvalue 0,000. Berdasarkan hasil uji Parameter Estimates variabel riwayat memiliki keluarga Penderita DM sangat berpengaruh terhadap pengetahuan mahasiswa dalam meberikan edukasi kepada penderita DM dengan Pvalue 0,003. Terdapat perbedaan Pengetahuan Baik sebelum dan sesudah diberikan diabetes self management education hal ini dipengaruhi oleh riwayat memiliki keluarga Penderita DM.Kata Kunci: diabetes melitus; pengetahuan; diabetes self management education